Humour Styles and Professional Burnout of Pedagogues Working in Juvenile Rehabilitation Centres - Karłyk-Ćwik, Anna (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The purpose of the research presented in this article was to diagnose the intensification of the burnout syndrome and its particular dimensions and humour styles presented by the teachers of juvenile rehabilitation centres, as well as establishing mutual relations between those variables. Our own research, carried out in the group of 109 counsellors and teachers employed in troubled teens group homes and juvenile centres revealed a low job burnout level and a high intensification of adaptive humour styles of the examined pedagogues. The conducted research, filling in the gap in scientific studies, confirmed also the existence of essential links between humour and a burnout in the professional functioning of pedagogues, confirming the conclusion that the positive adaptive humour can be an important element of the prevention against the risk of burning out.